2014
DOI: 10.1371/journal.pone.0115953
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Markers Associated with Verticillium Wilt Resistance in Alfalfa (Medicago Sativa L.) Using High-Resolution Melting

Abstract: Verticillium wilt, caused by the soilborne fungus, Verticillium alfalfae, is one of the most serious diseases of alfalfa (Medicago sativa L.) worldwide. To identify loci associated with resistance to Verticillium wilt, a bulk segregant analysis was conducted in susceptible or resistant pools constructed from 13 synthetic alfalfa populations, followed by association mapping in two F1 populations consisted of 352 individuals. Simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
13
2
Order By: Relevance
“…In the present study, two were identified on chromosome 6 and one on chromosome 7, suggesting similar locations of loci for VW resistance in M. sativa and M. truncatula . However, additional resistance loci to VW have also been identified in M. sativa by both our previous (Zhang et al ., ) and present studies, whereas these loci were not found in M. truncatula . For instance, several VW resistance loci were identified on chromosome 8 by both our previous (Zhang et al ., ) and present studies, whereas no VW resistance locus has been reported on chromosome 8 in M. truncatula .…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…In the present study, two were identified on chromosome 6 and one on chromosome 7, suggesting similar locations of loci for VW resistance in M. sativa and M. truncatula . However, additional resistance loci to VW have also been identified in M. sativa by both our previous (Zhang et al ., ) and present studies, whereas these loci were not found in M. truncatula . For instance, several VW resistance loci were identified on chromosome 8 by both our previous (Zhang et al ., ) and present studies, whereas no VW resistance locus has been reported on chromosome 8 in M. truncatula .…”
Section: Discussioncontrasting
confidence: 59%
“…They include a major QTL on chromosome 7, and two minor QTLs on chromosomes 2 and 6 (Ben et al ., ). In our previous study, three resistance loci associated with VW resistance were identified on chromosome 7 and one on chromosome 2 (Zhang et al ., ). In the present study, two were identified on chromosome 6 and one on chromosome 7, suggesting similar locations of loci for VW resistance in M. sativa and M. truncatula .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations